Adaptability of Miscanthus Cultivars for Biomass Production - J. L. Moyer (Kansas Agricultural Experiment Station Research Reports, 2016)
In 2015, miscanthus dry matter (DM) did not differ between cultivars, averaging 10,250 lb DM/a. Total three-year production for the cultivars was also similar, averaging 26,170 lb/a.
Keywords: pastures; hay